Long non-coding RNA CCAL regulates colorectal cancer progression by activating Wnt/β-catenin signalling pathway via suppression of activator protein 2α. Issue 9 (20th May 2015) - Ma, Yanlei; Yang, Yongzhi; Wang, Feng; Moyer, Mary-Pat; Wei, Qing; Zhang, Peng; Yang, Zhe; Liu, Weijie; Zhang, Huizhen; Chen, Niwei; Wang, Hua; Wang, Huamin; et al.
Abstract : Objective: Long non-coding RNAs (lncRNAs) are emerging as key molecules in cancers, yet their potential molecular mechanisms are not well understood. The objective of this study is to examine the expression and functions of lncRNAs in the development of colorectal cancer (CRC). Methods: LncRNA expression profiling of CRC, adenoma and normal colorectal tissues was performed to identify tumour-related lncRNAs involved in colorectal malignant transformation. Then, we used quantitative reverse transcription PCR assays to measure the tumour-related lncRNA and to assess its association with survival and response to adjuvant chemotherapy in 252 patients with CRC. The mechanisms of CCAL function and regulation in CRC were examined using molecular biological methods. Results: We identified colorectal cancer-associated lncRNA (CCAL) as a key regulator of CRC progression. Patients whose tumours had high CCAL expression had a shorter overall survival and a worse response to adjuvant chemotherapy than patients whose tumours had low CCAL expression. CCAL promoted CRC progression by targeting activator protein 2α (AP-2α), which in turn activated Wnt/β-catenin pathway. CCAL induced multidrug resistance (MDR) through activating Wnt/β-catenin signalling by suppressing AP-2α and further upregulating MDR1/P-gp expression. In addition, we found that histone H3 methylation and deacetylases contributed to the upregulation of CCAL in CRC. Conclusions: Our results suggest that CCAL is a crucial oncogenic regulator involved in CRC tumorigenesis and progression.